2023
DOI: 10.1038/s41419-023-06250-9
|View full text |Cite
|
Sign up to set email alerts
|

Classification, function, and advances in tsRNA in non-neoplastic diseases

Liou Zhang,
Jie Liu,
Yang Hou

Abstract: AbstracttRNA-derived small RNAs (tsRNAs) are non-coding small RNAs produced by specific endonucleases following the processing and splicing of precursor or mature tRNAs upon starvation, oxidative stress, hypoxia, and other adverse conditions. tRNAs are classified into two major categories, tRNA fragments (tRFs) and tRNA-derived stress-induced small RNAs (tiRNAs), based on differences in splice sites. With the development of high-throughput sequencing technologies in recent years, tsRNAs have been found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…tRNA-derived small RNAs (tsRNAs) are a class of small non-coding RNAs derived from different regions of tRNA, including the 5 ′ end, 3 ′ end, and internal regions. tsRNAs can regulate gene expression and thereby influence important biological processes such as cell proliferation, differentiation, and apoptosis [138]. One study has demonstrated that tsRNA-26576 is highly expressed in breast tissues and functions in promoting tumor cell proliferation and inhibiting tumor cell apoptosis [139].…”
Section: Other Types Of Ncrna and Tumor Angiogenesismentioning
confidence: 99%
“…tRNA-derived small RNAs (tsRNAs) are a class of small non-coding RNAs derived from different regions of tRNA, including the 5 ′ end, 3 ′ end, and internal regions. tsRNAs can regulate gene expression and thereby influence important biological processes such as cell proliferation, differentiation, and apoptosis [138]. One study has demonstrated that tsRNA-26576 is highly expressed in breast tissues and functions in promoting tumor cell proliferation and inhibiting tumor cell apoptosis [139].…”
Section: Other Types Of Ncrna and Tumor Angiogenesismentioning
confidence: 99%
“…Depending on the different cleavage sites of tRNAs, tRFs can be divided into tRF-1, tRF-2, tRF-3, tRF-5 and i-tRF, and tiRNA can be classified into 5'-tiRNA and 3'-tiRNA 2 , 5 . Extensive research has confirmed that tsRNA can act as functional molecules, thereby affecting the progression of diseases 6 - 9 .…”
Section: Introductionmentioning
confidence: 99%